How Much Information Is Enough? Comparing Agricultural Teletext With Other Media - Hernando Gonzalez (Journal of Applied Communications, 1988)
The question, "How much information is enough?" has received little research attention. Many researchers have encouraged more information for the "media poor" but have not examined how the "media rich" cope with ever-increasing amounts of media and messages, particularly when they need periodic updates of information. A five-month agricultural teletext field study by the University of Wisconsin-Extension identified, on a preliminary basis, what contents farmers and agribusiness people may be interested in, and how this electronic magazine compared with other agricultural mass media. These two audiences, who need periodically updated information as part of their work, read weather and market stories the most. They also rated teletext better or the same as other media in terms of convenience, timeliness and completeness.